A THEORETICAL MODEL OF PARENTAL FACTORS AND STUDENTS’ CAREER DECISIONS TO JOIN THE HOSPITALITY INDUSTRY IN CHINA - Hui ZHANG; Basri RASHID; Abdul Alem MOHAMMED (Geo Journal of Tourism and Geosites, 2017)
China is now enjoying fast growth of international tourism development, which contributes to creating a large amount of employment in the tourism and hospitality industry. For the sake of gaining competitive advantage, this industry has an urgent need to attract and recruit the qualified and skilled employees. However, a great proportion of Hospitality and Tourism Management (HTM) undergraduates fail to make their career decisions to work in the tourism industry due to the parental influential factors. It is therefore important to provide a value conceptual 1 model that expounds on the theoretical relationships existing between two parental factors and HTM students’ career intentions. This study contributes to the literature by clarifying the effects of parental influence on the students’ career decisions to enter the hospitality industry in China.